Multi-cellular network model predicts alterations in glomerular endothelial structure in diabetic kidney disease - Patidar, Krutika; Ford Versypt, Ashlee N. (PLOS Computational Biology, 2025)
The progression of diabetic kidney disease is often characterized by early dysfunction of glomerular endothelial cells, including alterations in fenestration size and number linked to impaired glomerular filtration. However, the cellular mechanisms regulating fenestrations in glomerular endothelial cells remain poorly understood due to limitations in existing in vitro models, challenges in imaging small fenestrations in vivo, and inconsistencies between in vitro and in vivo findings. This study used a logic-based protein-protein interaction network model with normalized Hill functions for dynamics to explore how glucose-mediated signaling dysregulation impacts fenestration dynamics in glomerular endothelial cells. Key drivers of fenestration loss and size changes were identified by incorporating signaling pathways related to actin remodeling, myosin light chain kinase, Rho-associated kinase, calcium, and VEGF and its receptors. The model predicted how hyperglycemia in diabetic mice leads to significant fenestration loss and increased size of fenestrations. Glycemic control in the pre-diabetic stage mitigated signaling dysregulation but was less effective as diabetic kidney disease developed and progressed. The model suggested alternative disease intervention strategies to maintain the integrity of the fenestration structure, such as targeting Rho-associated kinase, VEGF-A, NFκB, and actin stress fibers.